The Subjects Required by Industries for Engineering Technology Students in Universiti Tun Hussein Onn Malaysia - Jalani, Jamaludin; Mashori, Sumaiya; Norjali, Rasida; Syafiq Sadun, Amirul (International Journal of Engineering and Technology, 2018)
This paper investigates the effectiveness of the Structured Internship Program (SIP) for engineering technology students in the Faculty of Engineering Technology (FTK), Universiti Tun Hussein Onn Malaysia (UTHM). Apart from 6 months training which is carried out during second (2) semester of year 4 (i.e. final semester), the SIP is an additional training component that takes place during the third (3rd) semester of year two (2) and year three (3) for two (2) months respectively. The SIP is developed mainly to enhance the engineering skills, particularly for the practical skills of FTK students. The practical experience has become one of the criteria for the majority of employers in selecting the potential students to work with them. This practical experience also allows the students to build the confidence in preparing the job interview. However, the effectiveness of the SIP is still required further investigation as the extra training may affect the performance of FTK students. An online survey has been carried out for 35 students after completing their training. The results show that majority of students satisfied with their training and considered to prolong their training period. They claim that the academic development, work skills development and work assignment are important aspects to be considered and monitored in order to improve their knowledge and skills after completing their industrial training. The survey clearly shows that a few suggestions have been made to improve the SIP and Industrial Training programme.Â Â